Glycosylation of H4 influenza strains with pandemic potential and susceptibilities to lung surfactant SP-D - Parsons, Lisa M.; Zoueva, Olga; Grubbs, Gabrielle; Plant, Ewan; Jankowska, Ewa; Xie, Yijia; Song, Hao; Gao, George F.; Ye, Zhiping; Khurana, Surender; Cipollo, John F. (Frontiers in Molecular Biosciences, 2023)
We recently reported that members of Group 1 influenza A virus (IAV) containing H2, H5, H6 and H11 hemagglutinins (HA), are resistant to lung surfactant D (SP-D). H3 viruses, members of Group 2 IAV, have high affinity for SP-D, which is dependent upon the presence of high mannose glycans at glycosite N165 on the head of HA. The low affinity of SP-D for the Group 1 viruses is due to the presence of complex glycans at an analogous glycosite on the head of HA and replacement with high mannose glycan at that site evoked strong interaction with SP-D. Thus, if members of Group 1 IAV were to make the zoonotic leap to humans, pathogenicity of such strains could be problematic since SP-D, as a first line innate immunity factor in the respiratory tissues, could be ineffective as demonstrated in vitro. Here we extend those studies to Group 2 H4 viruses that are representative of those with specificity for avian or swine sialyl receptors, namely those with receptor binding sites (RBS) with either Q226 and G228 for avian or recent Q226L and G228S mutations that facilitate swine receptor specificity. The latter have increased pathogenicity potential in humans due to a switch from avian Sialyl2,3- to Sialyl2,6 glycan receptor preference. A better understanding of SP-D potential action against these strains will provide important information regarding pandemic risk of such strains. Our glycomics and in vitro analyses of four H4 HAs reveal SP-D favorable glycosylation patterns. Therefore, susceptibilities to this first line innate immunity defense respiratory surfactant against such H4 viruses is high and aligns with H3 HA glycosylation.